Chemistry In Context: Applying Chemistry To Society - Pryde Eubanks Lucy (McGraw -Hill, 2005)
The laboratory manual is intended to accompany the fifth edition of Chemictry in Context, Applying Chemistry to Society. That text and this laboratory manunal have been designed speccifically for college students majoring in disciplines outside of the natural science. The text examines s seclected set of scienen and technology issues with broadder societal impications; thics manual provides laboratory experiences that are relevant to those topics. Our object in writing this manual was not to train future chemists, but rather to show what chemists do and how they do it. We also woul like for you to appreciate the fact that there is not great nystery to doing chemisty tin te laboratory. A great deal of chemical information about the world around you can be abtained with simple chamiical equipment and simple procadures.